Readiness of a future geography teacher to use ICT in the educational process - Hevko, Igor Vasilievich (Journal of Education, Health and Sport, 2019)
The article is devoted to the current problem of professional training of a future teacher for the use of ICT in a geography lesson. The article describes the main features of the organization of professional training of future geography teachers for the use of ICTs, which form a complex of professionally significant teacher skills aimed at teaching students how to work with all ICT components. The article describes the possibility of theoretical and pedagogical training of future teachers for learning to use ICT in the lessons effectively, thanks to the use of discussion technologies that allow you to activate the cognitive activity of students, as well as update knowledge in the field of ICT use in a geography lesson. Also, I’ll take a look at ICT for half an hour of self-work robots. Practical ikosuvannya ІКТ is possible at an hour of passing pedagogical practice in schools.